The Influence of Non-Performed Financing (NPF), Operational Costs, Financing to Deposit Ratio (FDR) and Net Operating Margin to Return on Assets at Indonesian Sharia Commercial Banks - Sofyan Halim; Mohamad Torik Langlang Buana (Falah: Jurnal Ekonomi Syariah, 2021)
This study aims to determine the influence of Non-Performed Financing (NPF), Operational Costs,  Financing to Deposit Ratio (FDR) and Net Operating Margin to Return on Assets at Indonesian Sharia Commercial Banks. This research was a quantitative using causal method to analyze the relationship between research variables. Data collected in this study from year 2016 to 2020 from the Financial Services Authority official website www.ojk. go.id. The result found that Non-Performed Financing (NPF), Operational Costs and Financing to Deposit Ratio (FDR) have no significant effect on Return on Assets. While Net Operating Margin has significant positive effect to Return on Assets at Indonesian Sharia Commercial Banks. This research is expected to provide a contribution that can be a solution, suggestion and recommendation that can be used as a reference for decision-makers, especially stakeholders of Sharia Commercial Banks in Indonesia.  The results of this study is expected to add the repertoire of scientific literature, especially studies on the management of sharia financial transactions.